Procedures in Federal Tax Controversies (Book). - Bruns, William J.; Vogel, Eugene L. (The Accounting Review, 1969)
Reviews the book "Procedures in Federal Tax Controversies," by Marvin Joseph Garbis and Robert L. Frome.